Energy-efficient distance-bounding with residual charge computation - ZHUANG, Yunhui (Institutional Knowledge at Singapore Management University, 2020)
Real-time location systems are often required in industrial applications. In addition to securely determining an item's location, these systems also need to accommodate energy-limited tracking tokens. Distance-bounding protocols enable a Verifier to cryptographically determine an upper-bound on the physical distance to a Prover by measuring the round-trip time of specially designed challenge-response messages. This type of protocols serve as countermeasure to three common attacks on location-based systems and have been extensively studied with the goal of achieving optimal security bounds for the respective attacks. In this paper, we propose a new energy-efficient distance-bounding protocol that protects against all three common attacks in a distance-bounding scenario with improved security bounds. We provide a new approach to combining the response registers and Prover's key to determine responses. Furthermore, the protocol design allows offline pre-computation of the function $f$f used to determine the Prover's response registers. This results in faster protocol execution, the reader does not wait for the tag to compute any cryptographic function during the protocol execution, and also allows passive tokens to effectively use residual energy after the preceding transaction to compute response registers for the next protocol run.